The Application of Main Component Analysis Method on Indicators of Romanian National Authority for Consumers Protection Activities - Manuela Rozalia Gabor; Daniela Ştefănescu; Lia Codrina Conţiu (Amfiteatru Economic Journal, 2010)
The National Authority for Consumers Protection, Romania (NACP Romania) is the institution which records various trends from one development region to another as well as from one county to another. The indicators of NACP Romania activities are firmly correlated with other important macroeconomic indicators, even at the level of Romanian counties, hypothesis verified by the authors in a previous research. (Stefanescu & Gabor, 2008) The paper tests the hypothesis that in the last decade there have been numerous structural changes regarding the economic indicators at county level and we will analyze the evolution of these structural changes in two different periods, respectively year 2000 and 2006, and especially the clustering of Romanian counties, taking into account the macroeconomic indicators and those recorded by NACP Romania, using a descriptive method of data analysis, the principal component analysis (PCA). By applying the PCA method, we can obtain useful information for NACP that, according to its specific tasks, cooperates with local government authorities regarding the development of consumer education strategy and the organization of control activities. In this regard, depending on the level of economic development of each county, the consumption characteristics of the population, the earnings level, as well as the GDP per capita, the NACP can develop differentiated strategies, adapted to the features of each county.
Keywords: C02; C1; C19; D02; D03; D12; D18; 330; The National Authority for Consumers Protection from Romania; principal component analysis; macroeconomic indicators; counties; correlation